Enforced DNA repair enzymes rescue neurons from apoptosis induced by target deprivation and axotomy in mouse models of neurodegeneration. (January 2017) - Martin, Lee J.; Wong, Margaret
Abstract: It is unknown whether DNA damage accumulation is an upstream instigator or secondary effect of the cell death process in different populations of adult postmitotic neurons in the central nervous system. In two different mouse models of injury-induced neurodegeneration characterized by relatively synchronous accumulation of mitochondria, oxidative stress, and DNA damage prior to neuronal apoptosis, we enforced the expression of human 8-oxoguanine DNA glycosylase (hOGG1) and human apurinic-apyrimidinic endonuclease-1/Ref1 (hAPE) using recombinant adenoviruses (Ad). Thalamic lateral geniculate neurons and lumbar spinal cord motor neurons were transduced by Ad-hOGG1 and Ad-hAPE injections into the occipital cortex and skeletal muscle, respectively, prior to their target deprivation- and axotomy-induced retrograde apoptosis. Enforced expression of hOGG1 and hAPE in thalamus and spinal cord was confirmed by western blotting and immunohistochemistry. In injured populations of neurons in thalamus and spinal cord, a DNA damage response (DDR) was registered, as shown by localization of phospho-activated p53, Rad17, and replication protein A-32 immunoreactivities, and this DDR was attenuated more effectively by enforced hAPE expression than by hOGG1 expression. Enforced expression of hOGG1 and hAPE significantly protected thalamic neurons and motor neurons from retrograde apoptosis induced by target deprivation and axotomy. We conclude that a DDR response is engaged pre-apoptotically in different types of injured mature CNS neurons and that DNA repair enzymes can regulate the survival of retrogradely dying neurons, suggesting that DNA damage and activation of DDR are upstream mechanisms for this form of adult neurodegeneration in vivo, thus identifying DNA repair as a therapeutic target for neuroprotection.